Hepatitis E virus is effectively inactivated in platelet concentrates by ultraviolet C light. Issue 7 (7th May 2020) - Praditya, Dimas; Friesland, Martina; Gravemann, Ute; Handke, Wiebke; Todt, Daniel; Behrendt, Patrick; Müller, Thomas H.; Steinmann, Eike; Seltsam, Axel
Abstract : Background and Objectives: As previous investigations have shown, THERAFLEX UV‐Platelets, a UVC‐based pathogen inactivation (PI) system, is effective against non‐enveloped transfusion‐relevant viruses such as hepatitis A virus (HAV), which are insensitive to most PI treatments for blood products. This study investigated the PI efficacy of THERAFLEX UV‐Platelets against HEV in platelet concentrates (PCs). Materials and Methods: Buffy coat‐derived PCs in additive solution were spiked with cell culture‐derived HEV and treated with the THERAFLEX UV‐Platelets system using various doses of UVC (0·05, 0·10, 0·15 and 0·20 (standard) J/cm 2 ). Titres of infectious virus in pre‐ and post‐treatment samples were determined using a large‐volume plating assay to improve the detection limit of the virus assay. Results: THERAFLEX UV‐Platelets dose‐dependently inactivated HEV in PCs. The standard UVC dose inactivated the virus to below the limit of detection, corresponding to a mean log reduction of greater than 3·5. Conclusion: Our study demonstrates that the THERAFLEX UV‐Platelets system effectively inactivates HEV in PCs.